Study on the volatilization of O-containing functional groups during the mild pyrolysis using Shengli brown coal - Wang, Y.; Zhou, J.; Xu, M.; Xu, D.; Zhang, Shu (2012)
The purpose of this paper is to investigate the change of the O-containing functional groups in Shengli (SL) brown coal upon to the pyrolysis at low temperatures and pressures. The amounts of different O-containing functional groups of SL brown coal and its resultant chars were mainly quantified by titration methods. SL brown coal was pyrolized under the conditions of 200~350°C and 1~5 MPa with holding time of 30~ 60 min. The results show that the oxygen mainly exists as carboxyl and hydroxyl functional groups in the coal, accounting for approximate 69 wt% of the total oxygen. At 300 or 350°C, the majority of carboxyl and methoxy which were mainly associated to aliphatic and side chains has disappeared, whilst more than 50% of phenolic hydroxyl group still remained in the coal at 350°C. The holding time from 30 to 60 min could cause ~10 wt% loss in phenolic hydroxyl group at 350°C. However, the effect of pressure within the range on the oxygen removal was ignorable, probably due to the low temperatures used.